Faktor-Faktor yang Mempengaruhi Kepuasan Pasien pada Puskesmas Suko Kecamatan Maron Kabupaten Probolinggo - Agustina Pujiastuti; Yekti Rahajeng; Sanol Nur Arifin (Fakultas Ekonomi Universitas Panca Marga, 2022)
Patient satisfaction is the main goal of the puskesmas. The purpose of this study was to examine the effect of both simultaneously and partially the quality of service and trust on patient satisfaction and to examine the dominant between service quality and trust on patient satisfaction. The object of research is at the Suko Public Health Center, Maron District, Probolinggo Regency. The research method uses a descriptive approach causal associative with a sample of 88 respondents, the method of collecting data using a questionnaire with a technique using incidental sampling. The analysis test with the validity test shows that all statement items are valid, namely above 0.205, the reliability test shows reliable results that are above 0.60., the classical assumption test, the normality test, shows the data is normally distributed, the multicollinearity test shows that the independent variable (X) and the dependent variable (Y) are not present. correlation between independent variables or regression models independent of multicollinearity, heteroscedasticity test showed no heteroscedasticity, autocorrelation test showed no autocorrelation. The F test shows that the independent variables have a simultaneous effect on satisfaction (Y) with a value of Fcount > Ftable (37.426 > 3.10) (sig. 0.000 < 0.05). The t test shows that the service quality variable (X1) has a partial effect on satisfaction (Y) with tcount > ttable (2,228>1,663) (sig. 0.000 0.05). And the trust variable (X2) has a partial effect on satisfaction (Y) with a value of tcount ttable (4.032 > 1.663) (sig. 0.000 0.05). Trust has a dominant effect on patient satisfaction.